Heterogeneous nucleation of Mg2Si on CaSb2 nucleus in Al–Mg–Si alloys. Issue 37 (7th October 2015) - Yu, Hong-Chen; Wang, Hui-Yuan; Chen, Lei; Liu, Feng; Wang, Cheng; Jiang, Qi-Chuan
<x xml:space="preserve">Abstract</x> Primary Mg2Si with a truncated octahedral morphology and size over a range of 8–15 μm were prepared by simultaneously adding Ca and Sb into the Al–Mg–Si melt.